Pengaruh Risiko Pembiayaan, Kecukupan Modal dan Dana Pihak Ketiga terhadap Profitabilitas pada Bank Syariah di Indonesia Tahun 2017-2021. - Risa Bela Eka Safitri; Dedi Suselo (Jurnal Mirai Management, 2023)
The stability of bank profitability is needed in financial institutions. A company certainly seeks to compete to produce good profitability. The level of profitability that fluctuates greatly affects the performance of a bank, especially at this time the condition of the bank is not all stable. This is based on the fact that profitability is one of the triggers in improving bank quality. Although the ups and downs of profitability are commonplace for banks. The purpose of this study is to describe the effect of financing risk, capital adequacy and third party funds on profitability. The method used in this study is an associative quantitative method. The population in this study are all Islamic banks in Indonesia. The samples taken were 6 Islamic banks. The data analysis technique used is using multiple linear regression tests. Based on the research results show that; (1) Financing risk has no effect on profitability. (2) Capital adequacy affects profitability. (3) Third party funds affect profitability. But simultaneously the three of these variables affect profitability. This shows that profitability has a significant impact on other variables. Keywords: Financing Risk, Capital Adequacy, Third Party Funds, Profitability.